Depolymerization of Kraft Lignin Using a Metal Chloride-Based Deep Eutectic Solvent: Pathways to Sustainable Lignin Valorization - Shubho Ghosh; Masud Rana; Jeong-Hun Park (Applied Sciences)
Driven by the urgent need for sustainable alternatives to fossil fuels, the focus on the exploration of lignocellulosic biomass, particularly lignin, as a promising renewable feedstock for biofuels and high-value chemicals has intensified. This study investigated the depolymerization of KL using a DES comprising ChCl and ZnCl2. Our analysis systematically focused on the effects of reaction temperature, time, and the DES-to-lignin ratio on the yields and characteristics of the products. Optimal KL depolymerization was observed at a temperature of 190 °C and a duration of 8 h, yielding a maximum liquid product yield of 54.44% and RL yield of 45.56%. The results revealed that increasing the reaction temperature enhanced the depolymerization process owing to a reduction in the viscosity of the DES, which improved mass transfer and interactions with lignin. Under these optimal conditions, the molecular weight of the bio-oil was considerably lower (Mw = 1498 g/mol and Mn = 1061 g/mol) than that of the bio-oil obtained without DES treatment (Mw = 1872 g/mol and Mn = 1259 g/mol), indicating a more favorable molecular weight distribution with DES treatment. Furthermore, elemental analysis revealed a reduction in the O, N, and S contents of the RL following DES treatment, increasing the high heating value from 24.82 MJ kg−1 for the non-DES-treated RL to 26.44 MJ kg−1 for the DES-treated RL. These findings underscore the potential of the (ChCl:ZnCl2) DES as a sustainable and effective medium for lignin valorization, paving the way for the synthesis of high-quality biofuels and chemicals from lignocellulosic biomass.